Analysis of Management Strategies of Staff-Authority Conflicts in Adekunle Ajasin University, Akungba-Akoko and Rufus Giwa Polytechnic Owo, Ondo State, Nigeria. - Michael Sunday AYEERUN (International Journal of Education, Teaching, and Social Sciences, 2022)
Abstract The study investigated the possible causes of conflicts in our tertiary institutions. The effects of conflicts were highlighted while the strategies to be employed in handling conflicts were extensively discussed. The survey design of the descriptive research type was employed in the study which was limited to two of the tertiary institutions owned by the Ondo State Government i.e. Adekunle Ajasin University Akungba-Akoko and Rufus Giwa Polytechnic Owo. 400 subjects were selected by stratified random sampling technique from the two institutions of the total staff and students’ population. The instrument used in gathering data is titled “Conflict Management Strategies Questionnaire” (CMSQ). The data collected were subjected to t-test analysis to test the two hypothesis generated at 0.05 level of significance, the results showed that there were no significant differences in the strategies employed by the Management of the University and the Polytechnic in managing Staff-Authority conflicts. The study revealed that conflict is inevitable in any organization but that it could be managed. Some recommendations were made to stem the tide of conflicts in our tertiary institutions of which attending to the needs of subordinates promptly by institutional leaders should be taken as the best strategy to curb conflicts. Keywords: Conflict, management, authority, strike, strategy.